Islamic Nations' Approaches to Combating Gender Discrimination against Women: An Examination of the Southeast Asia Region - Ahmad, Nehaluddin; Zamri, Zheimie H.; Omarali, Noor Saffrena (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2024)
Gender-based discrimination remains a pervasive issue despite gender equality being recognised as a fundamental human right. In Southeast Asia, where over two hundred and forty million Muslims reside, the challenge of gender discrimination continues to affect women, although Islam serves as the predominant religion. This study examines the policy and legal reforms adopted by Islamic nations in Southeast Asia—Specifically Malaysia, Brunei, Indonesia, Thailand (Southern Thailand), and the Philippines—in their effort to combat gender discrimination. This research mainly aims to assess the effectiveness of these reforms in addressing both legal frameworks and cultural practices that contribute to the marginalisation of women. Through qualitative analysis of policy documents, legal texts, official reports and academic reports, this study explores the reforms in key sectors such as employment, healthcare, family law, and political representation. Key findings highlight significant reforms, such as Brunei's national action plan for women's empowerment, Malaysia’s comprehensive public sector measures for gender equality, Indonesia's gender mainstreaming policies, and Thailand’s legal protections against gender discrimination. Despite these efforts, the study reveals persistent challenges, including limited political representation of women, cultural barriers, and inconsistent enforcement of legal reforms. The findings indicate that while progress has been made, the full realisation of gender equality requires continued legal reform, stronger policy implementation, and greater societal transformation. This research contributes to the broader discourse on Islamic legal perspectives and policy-making, offering insights into the intersection of religion, law, and gender equality. The study also provides recommendations for enhancing legal frameworks to achieve greater gender equity in the region.